2004
DOI: 10.2337/diabetes.53.4.1074
|View full text |Cite
|
Sign up to set email alerts
|

Hexosamine Pathway Is Responsible for Inhibition by Diabetes of Phenylephrine-Induced Inotropy

Abstract: Hyperglycemia diminishes positive inotropic responses to agonists that activate phospholipase C (PLC) and generate inositol trisphosphate (1,4,5). The mechanisms underlying both the inotropic responses and hyperglycemia's effects on them remain undetermined, but data from isolated cardiomyocytes suggest the involvement of capacitative Ca 2؉ entry (CCE), the influx of Ca 2؉ through plasma membrane channels activated in response to depletion of endoplasmic or sarcoplasmic reticulum Ca 2؉ stores. In neonatal rat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 53 publications
2
58
0
Order By: Relevance
“…In contrast, inhibition of NCX, which is also reportedly activated by PE (116), had no effect on PEinduced inotropic response (82). Notably, SKF96365 had no effect on the positive inotropic response to the ␤-adrenergic agonist isoproterenol, demonstrating that SOCE appears to be specific in mediating the effects of ␣-adrenergic and not ␤-adrenergic agonists (82). This specificity is likely due to the fact that unlike ␣-adrenergic agonists, ␤-adrenergic agonists do not generate IP 3 and do not lead to Ca 2ϩ store depletion.…”
Section: Orai1/trpcmentioning
confidence: 54%
See 2 more Smart Citations
“…In contrast, inhibition of NCX, which is also reportedly activated by PE (116), had no effect on PEinduced inotropic response (82). Notably, SKF96365 had no effect on the positive inotropic response to the ␤-adrenergic agonist isoproterenol, demonstrating that SOCE appears to be specific in mediating the effects of ␣-adrenergic and not ␤-adrenergic agonists (82). This specificity is likely due to the fact that unlike ␣-adrenergic agonists, ␤-adrenergic agonists do not generate IP 3 and do not lead to Ca 2ϩ store depletion.…”
Section: Orai1/trpcmentioning
confidence: 54%
“…In addition to stimulating cardiomyocyte hypertrophy, PE, an ␣-adrenergic agonist, is a potent positive inotropic agent in the heart. Interestingly, we reported that treatment of the isolated perfused heart with the SOCE inhibitor SKF96365 significantly blunted the response to PE compared with untreated control hearts (82). In contrast, inhibition of NCX, which is also reportedly activated by PE (116), had no effect on PEinduced inotropic response (82).…”
Section: Orai1/trpcmentioning
confidence: 96%
See 1 more Smart Citation
“…In the intact heart, increased HBP flux induced by either short-term STZ-induced diabetes or after acute glucosamine treatment blunted the positive inotropic responses to the ␣-adrenergic agonist PE, whereas the response to ␤-adrenergic stimulation was unaffected (168). In ventricular myocytes, increased O-GlcNAcylation attenuated the increase in cytosolic Ca 2ϩ levels induced by PE and other IP 3 -generating agonists such as angiotensin II (157,169).…”
Section: O-glcnacylation and Cardiomyocyte Dysfunctionmentioning
confidence: 88%
“…First described in nonexcitable cells, CCE has now been shown to coexist with L-type channels in smooth and skeletal muscle cells (17,35) and in both neonatal and adult cardiomyocytes (12,13,31). The TRPC protein family has been a prime candidate for CCE channel proteins (14) and TRPC1, -3, -4, -5, and -6 have all been identified in rat and mouse hearts (14,28,30).…”
Section: Discussionmentioning
confidence: 99%